2016
DOI: 10.1038/nrrheum.2016.178
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and adenosine receptors in the pathogenesis and treatment of rheumatic diseases

Abstract: Adenosine, a nucleoside derived primarily from the extracellular hydrolysis of adenine nucleotides, is a potent regulator of inflammation. Adenosine mediates its effects on inflammatory cells by engaging one or more cell-surface receptors. The expression and function of adenosine receptors on different cell types change during the course of rheumatic diseases, such as rheumatoid arthritis. Targeting adenosine receptors directly for the treatment of rheumatic diseases is currently under study; however, indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
169
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(178 citation statements)
references
References 179 publications
(150 reference statements)
3
169
0
6
Order By: Relevance
“…We observed a comparable effect of adenosine and the A 2A R agonist CGS21680 on the chemotaxis of HNSCC CD8 + T cells, suggesting that differences in the adenosine signaling pathway and not adenosine degradation are responsible for the heightened effect of adenosine on chemotaxis. It is well established that A 2A R mediates the effect of adenosine in human T cells (5, 17, 5153). We have previously shown that adenosine inhibits the motility of human CD3 + T cells and cytokine release through A 2A R stimulation, activation of adenylyl cyclase and PKAI, and ultimately inhibition of KCa3.1 channels (22).…”
Section: Discussionmentioning
confidence: 99%
“…We observed a comparable effect of adenosine and the A 2A R agonist CGS21680 on the chemotaxis of HNSCC CD8 + T cells, suggesting that differences in the adenosine signaling pathway and not adenosine degradation are responsible for the heightened effect of adenosine on chemotaxis. It is well established that A 2A R mediates the effect of adenosine in human T cells (5, 17, 5153). We have previously shown that adenosine inhibits the motility of human CD3 + T cells and cytokine release through A 2A R stimulation, activation of adenylyl cyclase and PKAI, and ultimately inhibition of KCa3.1 channels (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although MTX has been used for several decades to reduce inflammation in patients with autoimmune disease, the mechanisms by which it does so are not fully understood. A leading hypothesis is that MTX directly inhibits an enzyme called AICAR transformylase, resulting in an increase in extracellular levels of adenosine, a potent anti-inflammatory mediator 14,45 . Other possible mechanisms that have been investigated suggest that MTX may affect cytokine production by immune cells, such as by decreasing the production of the proinflammatory cytokine TNFα 46 or increasing the production of the α-inflammatory cytokine IL-10 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of proinflammatory mediators in degenerated discs upregulates the expression of matrix-degrading enzymes [Risbud and Shapiro, 2014]. Since adenosine is also known as a potent endogenous inhibitor of inflammatory processes in the human body [Fredholm et al, 1994;Linden, 2005;Hasko et al, 2008;Hasko and Cronstein, 2013;Cronstein and Sitkovsky, 2017], adenosine can be a potential therapeutic agent for disc degeneration. …”
Section: Effect Of Adenosine On Intervertebral Disc Cellsmentioning
confidence: 99%
“…Anti-inflammatory activities of adenosine are primarily medicated through the adenosine A2A receptor [Tesch et al, 2004;Cronstein and Sitkovsky, 2017]. In addition, activation of AMPK has also been shown to exhibit anti-inflammatory effects [Mancini et al, 2017].…”
Section: Effect Of Adenosine On Intervertebral Disc Cellsmentioning
confidence: 99%
See 1 more Smart Citation